1991
DOI: 10.1021/jm00112a037
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant activity of 6-cyano-2,2-dimethyl-2H-1-benzopyran-4-carboxamides and -thiocarboxamides and their analogs in guinea pig trachealis

Abstract: Structural modifications of the potassium channel activator cromakalim (1) are described in which the amide moiety at C-4 has been replaced by carboxamide and thiocarboxamide functions. Analogues in which the hydroxyl group at C-3 has been oxidized or removed are also disclosed. Such analogues display an interesting profile of smooth muscle relaxant activity in the guinea pig isolated trachea, not all of which appears to result from the opening of potassium channels, but few compounds retain useful in vivo act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Further, we have shown that such agents (e.g., BMS-180448) can protect the ischemic myocardium without hemodynamic changes,9-16 thus validating the selectivity data in vitro. These types of cardiac Scheme Ia 32b (10,11) 32c (12,13) 32d (15,16) 32e (17,18) 32f (23,24) 32g (25,26) 32h ( 27) 32i (28, 29) 32J (30, 31) a Numbers in parentheses correspond to the products prepared from 32; for R'-R3, X, and Y, see Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we have shown that such agents (e.g., BMS-180448) can protect the ischemic myocardium without hemodynamic changes,9-16 thus validating the selectivity data in vitro. These types of cardiac Scheme Ia 32b (10,11) 32c (12,13) 32d (15,16) 32e (17,18) 32f (23,24) 32g (25,26) 32h ( 27) 32i (28, 29) 32J (30, 31) a Numbers in parentheses correspond to the products prepared from 32; for R'-R3, X, and Y, see Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Preischemia or predrug contractile function, heart rate (HR), and coronary flow (extracorporeal electromagnetic flow probe; Carolina Medical Electronics, King, NC) were measured. The hearts were pretreated with vehicle (0.04% dimethyl sulfoxide, DMSO) or 1-30 µ test compound (except 18 which was tested up to 200 µ ) (n = 4/group). The respective drug or vehicle treatment was continued for 10 min prior to the initiation of ischemia, and the agents were administered as a solution in the perfusate.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, further efforts were devoted to preparing the substituted analogs 15-17 of 12 with the aim of suppressing its metabolism via 4-hydroxylation. While similar in vasorelaxant potencies, the 4-chloro (15) and 4-fluoro (16) analogs showed slightly improved anti-ischemic potencies over 12. The 4-(trifluoromethyl) analog 17 was less active than 12 in both assays.…”
mentioning
confidence: 93%
“…The urea (10) and thiourea (11) analogs were prepared according to published procedures. 15 Supplementary Material Available: Experimental procedures and spectral data for 5-8,12-19 and procedures for the biological assays (8 pages). Ordering information is given on any current masthead page.…”
mentioning
confidence: 99%